The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Mind the gap: a comparative study of migratory behavior in social amoebae - Owen M. Gilbert; Jennie J. Kuzdzal-Fick; David C. Queller; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 2012)

Why are larvae of the social parasite wasp Polistes sulcifer not removed from the host nest? - R. Cervo; F. R. Dani; C. Cotoneschi; C. Scala; I. Lotti; J. E. Strassmann; D. C. Queller; S. Turillazzi (Behavioral Ecology and Sociobiology, 2008)

Larval sex identification in the paper wasp Polistes dominulus (Vespidae, Hymenoptera) - C. Cotoneschi; F. Scognamiglio; C. Scala; R. Cervo; J. E. Strassmann; S. Turillazzi (Insectes Sociaux, 2007)

Social parasitism of Polistes dominulus by Polistes nimphus (Hymenoptera, Vespidae) - R. Cervo; C. Stemmer; W. Castle; D. Queller; J. E. Strassmann (Insectes Sociaux, 2004)

Conflict over male parentage in stingless bees - E. Tth; D. C. Queller; A. Dollin; J. E. Strassmann (Insectes Sociaux, 2004)

Low relatedness and frequent queen turnover in the stenogastrine wasp Eustenogaster fraterna favor the life insurance over the haplodiploid hypothesis for the origin of eusociality - M. Landi; D. C. Queller; S. Turillazzi; J. E. Strassmann (Insectes Sociaux, 2003)

Co‐occurrence in nature of different clones of the social amoeba, Dictyostelium discoideum - A. Fortunato; J. E. Strassmann; L. Santorelli; D. C. Queller (Molecular Ecology, 2003)
The social amoeba, Dictyostelium discoideum , produces a multicellular fruiting body and has become a model system for cell–cell interactions such as signalling, adhesion and development. However, unlike most multicellular organisms, it forms by aggregation of cells and, in the laboratory, forms genetic chimeras where there may be competition among clones. Here we show that chimera formation is also likely in nature, because different clones commonly co‐occur on a very small scale. This suggests that D. discoideum will likely have evolved strategies for competing in chimeras, and that the function of some developmental genes will be competitive. Natural chimerism also makes D. discoideum a good model organism for the investigation of issues relating to coexistence and conflict between cells.

Swarm‐founding in the polistine wasps: the importance of finding many microsatellite loci in studies of adaptation - M. T. Henshaw; J. E. Strassmann; D. C. Queller (Molecular Ecology, 2001)
We developed 52 microsatellite loci for the wasp, Polybioides tabidus , for the purpose of studying the evolution and inclusive fitness consequences of swarm‐founding. The large number of loci is important for three reasons that may apply to many other systems. Heterozygosity was low in our target species, yet we found enough polymorphic loci for accurate kinship studies in this species. Many monomorphic loci were polymorphic in other polistine wasps, making comparative studies possible. Finally, enough loci amplified over a broad range of species to add a historical dimension. We sequenced six loci in other polistine wasps and used the flanking sequences to construct a phylogeny. Based on this phylogeny, we infer that swarm‐founding has evolved independently three times in the polistine wasps.

The independent origin of a queen number bottleneck that promotes cooperation in the African swarm-founding wasp, Polybioides tabidus - M. T. Henshaw; J. E. Strassmann; D. C. Queller (Behavioral Ecology and Sociobiology, 2000)

Absence of within-colony kin discrimination: foundresses of the social wasp, Polistes carolina , do not prefer their own larvae - J. E. Strassmann; P. Seppä; D. C. Queller (The Science of Nature, 2000)

The genetic structure of swarms and the timing of their production in the queen cycles of neotropical wasps - JOAN E. STRASSMANN; KEITH F. GOODNIGHT; CEAL J. KLINGLER; DAVID C. QUELLER (Molecular Ecology, 1998)
Kin selection theory has received some of its strongest support from analyses of within‐colony conflicts between workers and queens in social insects. One of these conflicts involves the timing of queen production. In neotropical wasps, new queens are only produced by colonies with just one queen while males are produced by colonies with more queens, a pattern favoured by worker interests. We now show that new colonies, or swarms, have few queens and variable within‐colony relatednesses which means that their production is not tied to new queen production. The queens in these swarms are seldom the mothers of the workers in the swarm. Therefore, either colonies producing swarms have very many queens, or queens joining daughter swarms are reproductive losers on the original colonies. As new colony production is not linked to queen production, it can occur at the ecologically optimum time, i.e. the rainy season. This disassociation between queen production and new colony production allows worker interests in sex ratios to prevail without hampering new colony production at the most favourable season, an uncoupling that may contribute to the ecological success of the Epiponini.

Colony life history and demography of a swarm-founding social wasp - J. E. Strassmann; Carlos R. Solís; C. R. Hughes; Keith F. Goodnight; David C. Queller (Behavioral Ecology and Sociobiology, 1997)

Control of reproduction in social insect colonies: individual and collective relatedness preferences in the paper wasp, Polistes annularis - David C. Queller; J. M. Peters; Carlos R. Solís; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 1997)

Trinucleotide microsatellite loci for a social wasp, Polistes - J. E. Strassmann; K. Barefield; C. R. Solís; C. R. Hughes; D. C. Queller (Molecular Ecology, 1997)